Adiposity among 132 479 UK Biobank participants; contribution of sugar intake vs other macronutrients. (12th July 2016) - Anderson, JJ; Celis-Morales, CA; Mackay, DF; Iliodromiti, S; Lyall, DM; Sattar, N; Gill, JMR; Pell, JP
Abstract: Background: Policy makers are being encouraged to specifically target sugar intake in order to combat obesity. We examined the extent to which sugar, relative to other macronutrients, was associated with adiposity. Methods: We used baseline data from UK Biobank to examine the associations between energy intake (total and individual macronutrients) and adiposity [body mass index (BMI), percentage body fat and waist circumference]. Linear regression models were conducted univariately and adjusted for age, sex, ethnicity and physical activity. Results: Among 132 479 participants, 66.3% of men and 51.8% of women were overweight/obese. There was a weak correlation (r = 0.24) between energy from sugar and fat; 13% of those in the highest quintile for sugar were in the lowest for fat, and vice versa. Compared with normal BMI, obese participants had 11.5% higher total energy intake and 14.6%, 13.8%, 9.5% and 4.7% higher intake from fat, protein, starch and sugar, respectively. Hence, the proportion of energy derived from fat was higher (34.3% vs 33.4%, P < 0.001) but from sugar was lower (22.0% vs 23.4%, P < 0.001). BMI was more strongly associated with total energy [coefficient 2.47, 95% confidence interval (CI) 2.36-2.55] and energy from fat (coefficient 1.96, 95% CI 1.91-2.06) than sugar (coefficient 0.48, 95% CI 0.41-0.55). The latter became negative after adjustment for total energy. Conclusions: Fat is the largest contributor to overall energy. The proportion of energy from fat in the diet, but not sugar, is higher among overweight/obese individuals. Focusing public health messages on sugar may mislead on the need to reduce fat and overall energy consumption.